Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1159/000070584
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cholesterol in Treatment-Resistant Depression

Abstract: Objective: Patients with major depressive disorder (MDD) may have significant differences in cholesterol levels compared with healthy controls. A previous study by our group reported that depressed patients with elevated cholesterol levels (≧200 mg/dl) were significantly more likely to be nonresponders to fluoxetine treatment than depressed patients with nonelevated cholesterol levels. However, very little is known regarding cholesterol in patients with treatment-resistant depression (TRD). The purpose of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 38 publications
4
23
0
1
Order By: Relevance
“…Statin treatment was shown to increase the tendency for depression; for example, simvastatin was shown to increase depression level significantly but did not affect anxiety level (Hyyppa et al 2003). In another study, depressive patients refractory to antidepressant treatment had significantly increased blood cholesterol level (Papakostas et al 2003). Patients with hypercholesterolemia had also the higher anxiety scores in the present study.…”
Section: Discussionsupporting
confidence: 44%
“…Statin treatment was shown to increase the tendency for depression; for example, simvastatin was shown to increase depression level significantly but did not affect anxiety level (Hyyppa et al 2003). In another study, depressive patients refractory to antidepressant treatment had significantly increased blood cholesterol level (Papakostas et al 2003). Patients with hypercholesterolemia had also the higher anxiety scores in the present study.…”
Section: Discussionsupporting
confidence: 44%
“…In one study (Papakostas et al 2003) a higher TG level was found in patients with TRD compared to non-TRD patients. Elevated cholesterol levels were associated with poor treatment response to noradrenergic antidepressants in TRD patients (Papakostas et al 2003).…”
Section: Discussionmentioning
confidence: 90%
“…In one study (Papakostas et al 2003) a higher TG level was found in patients with TRD compared to non-TRD patients. Elevated cholesterol levels were associated with poor treatment response to noradrenergic antidepressants in TRD patients (Papakostas et al 2003). A poor treatment response and high cholesterol levels were also observed in patients with MDD treated with SSRI fluoxetine (Iosifescu et al 2005) or paroxetine (Muck-Seler et al 2011).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Cholesterol is an important component in the structure of cell membrane, and plays a critical role in many functions in neural circuits, thus regulating mood state and antidepressant response (De Berardis et al, 2009;Papakostas et al, 2003;Pucadyil and Chattopadhyay, 2006). These functions include monoaminergic neurotransmission, energy metabolism, and synaptic plasticity (Bjork et al, 2010;Maxfield and Tabas, 2005;Sebastiao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%